Biomass carbon stock and water yield of teak catchments - Tyas Mutiara Basuki; Irfan Budi Pramono; Diah Auliyani (Brawijaya University, 2020)
Rehabilitation of degraded forests and lands using the vegetative method can be used to improve the environmental condition and sequestered carbon dioxide from the atmosphere. However, improper plant selection may create water shortage in dry season. Based on the background, the research was conducted in order to study the relationships of biomass carbon stock, evapotranspiration, and water yield of five catchments covered by various teak areas. The study was conducted in Blora Regency, Central Java, Indonesia. The percentage of mature teak plantation areas in the catchments were 82, 82, 73, 70, and 53%. The biomass carbon stock in each catchment was estimated using previously published data. The water yield of the catchments was calculated from the conversion of the stream water level at the outlet of each catchment. The evapotranspiration was calculated based on a simple water budget of a catchment. The results showed that the highest carbon stock was 64 t/ha and found in Modang Catchment (82% mature teak). The lowest carbon stock was 22 t/ha and measured in Gagakan Catchment (53% mature teak). In parallel with the amount of carbon stock, the highest evapotranspiration was measured in Modang Catchment, and the lowest was found in Gagakan Catchment. The observation of water yield during 2008- 2019 showed that the higher the carbon stock in the catchments, the lower the water yield. Synergy in reducing CO2 emission and sustaining water flows can be achieved by considering land suitability for plant growth and applying water conservation in forests and lands rehabilitation.